Fenomena Munculnya Interlanguage (Inglish) di Indonesia - Rosita Ambarwati (Jurnal Pendidikan, 2009)
The process of learning a new language is difficult. Even so, when the second language is finally formed, the language would have a continuous effect on the person’s mother tongue ability (Association for Psychological Science, 2009). On the other side, someone who is learning a new language, would also have trouble to understand the grammar in translation. In the translation skill, they move from the original language to the literal gloss before it reaches the new language (Saygin, 2001). Both sides show the same symptom, the birth of new terms that are actually combinations from both language elements. Some nations, suffer some sort of desperation where it is so difficult to learn English that leads them to a compromise. The compromise gave birth to numerous and vary new vocabularies, and almost can be recognizable as a language.